PERANCANGAN SISTEM INFORMASI PENGARSIPAN INTERNAL BERBASIS VISUAL BASIC DI BANK BRI UNIT TELUK JAMBE KAB.KARAWANG - Kartika Mayangsari, putri; Abu Bakar Sidik, Haris; Ponco Subagyo, Catur (INFOKOM (Informatika & Komputer), 2024)
In carrying out business activities in a company requires the existence of a strategic plan that involves technology and information to achieve company targets that have been made. Bank BRI itself is one of the largest banks in Indonesia serving the services and finance sector, while the products owned by Bank BRI are such as savings, time deposits, and credit loans. In daily operational activities at BRI, the results of customer transactions will produce documents that must be neatly organized and archived to make it easier for employees if at any time the documents are needed. Document archive management that is still manual makes document archives not neat and difficult to find when needed, this affects the service system to be hampered. Therefore, proper strategic planning is needed. The purpose of this research is to build a desktop-based computerized filing system with the application of Visual Basic. The results of this study indicate that with the system that has been built, employees at BRI Bank Telukjambe Karawang unit are helped by the problems they face.Keywords: Design, Archiving and , Visual Basic.